A Time Bomb of Child Health Hazards in Coastal Areas: Where is the Role of Puskesmas? (Case Study of Kampung Nelayan Seberang Medan Belawan) - Annisa Zahara (BKM Public Health and Community Medicine, 2024)
Purpose: Water pollution by heavy metals, notably lead, in Belawan waters, particularly in Kampung Nelayan Seberang, Medan Belawan, has reached critical levels. Research indicates leads levels at 0.270 mg/L, far exceeding the safe limits of 0.005 mg/L for lead. Consumption of contaminated fish can impede nutrient absorption in children, potentially leading to stunting. In 2022, Medan Belawan accounted for 26% of stunting cases in Medan City. Evaluating the Puskesmas Medan Belawan performance through Mintzberg’s organizational theory reveals suboptimal functioning in addressing these health impacts. Methods: This study utilized a case study approach to evaluate the role of Puskesmas Medan Belawan in mitigating the health impacts of heavy metal pollution. The evaluation of Puskesmas’s organizational function was based on Mintzberg’s five main function. Results: Analysis revealed the lead and cadmium concentrations in water and fish surpassed safe limits. The operating core function, executed by sanitarians, is confined to managing health center waste, neglecting heavy metal contamination. The technostructure function, responsible for monitoring and evaluating seawater quality standards, has also proven ineffective. The nutrition program remains passive, inadequately addressing the needs of Kampung Nelayan Seberang. According to Mintzberg's theory, the non-optimal performance of Puskesmas Medan Belawan in addressing this issue is evident from the ineffective operating core and technostructure functions. Enhancing effectiveness requires innovative, proactive environmental health and nutrition programs. Environmental health officers should routinely investigate the heavy metal content in water and fish consumed by Kampung Nelayan Seberang residents. Nutrition officers should provide regular iron supplements to children and pregnant women, considering that iron-deficient children absorb significantly more lead. Conclusion: Strengthening the core functions of operations, technological structure, and support staff at Puskesmas Medan Belawan is essential. Without these measures, ongoing heavy metal exposure poses severe long-term health risks for the community.